Penerapan teknologi rekayasa konstruksi wadah budi daya rumput laut bagi masyarakat di Pulau Nain - Ngangi, Edwin L. A.; Kreckhoff, Reni L.; Gerung, Grevo S. (e-Journal BUDIDAYA PERAIRAN, 2019)
The Higher Education Community Empowerment Program (PPMUPT) activity aimed to disseminate research results on design engineering and construction materials for verticultural cultivation of seaweed; Seed quality from seaweed cultivation centers in North Sulawesi; and Co-cultivation of seaweed and sea tilapia. The implementation partnered with the Nain Princess and Mekar Laut Groups, and was supported by the Nain Village Government. The three partners expressed their willingness and ability to work together in formulating and finding solutions to problems, as well as planning the implementation stages and all of these activities. In addition, partners continue to contribute throughout the activity. Formulation of problems with partners, are: Is there a technology that can minimize disease attacks on seaweed. The solution is in the form of: a. Engineering design and construction material for cultivation containers, b. Verticultural cultivation of engineering methods. The method applied was the classical and individual approach in the form of class lectures, demonstrations, and practices about the innovation of seaweed cultivation technology. The outputs of the PPMUPT activities were productive economic partners that have increased knowledge, skills, quality, quantity, and types of products. Participants were principally satisfied with this PPMUPT activity, and even 92.86% stated that they were very satisfied in participating in PPMUPT activities regarding the use of strings as ris ropes with seaweed verticulture methods.